Hydrogen supply via power‐to‐gas application in the renewable fuels regulations of petroleum fuels. (14th March 2019) - Alsubaie, Abdullah A.; Fowler, Michael; Elkamel, Ali
Abstract: Power‐to‐gas (PtG) is an evolving energy storage technique that can transfer surplus and intermittent renewable generated power into a marketable hydrogen, among other ancillary services for the electrical grid. This study provides a comparative assessment of blending 10 % corn‐ethanol and using an electrolytic hydrogen supply via PtG on the well to wheel of gasoline fuel, based on Ontario's energy system. The analysis is performed using the GREET ® model to investigate the energy and emissions results of the subject comparison. Consequently, PtG renewable hydrogen, when used for gasoline production, is found to decrease 4.6 % of the natural gas consumption of the gasoline cycle and, therefore, increase the renewable content of gasoline. Furthermore, the deployment of electrolytic hydrogen at the refinery results in minimizing gasoline carbon intensity by 0.15 kg CO2 e per 100 km (0.5 g CO2 e per MJ) of the fuel. When associated with the annual gasoline sales in Ontario, the use of electrolytic hydrogen can offer a reduction of 0.26 MT of greenhouse gas emissions yearly. Moreover, the hydrogen supply from the PtG method used for gasoline production may contribute to lowering VOCs, NOx, PM10, and PM2.5 criteria air pollutants from the gasoline cycle, which cannot be achieved with blending corn‐based ethanol. Therefore, the results of this paper support the inclusion of the PtG concept in renewable fuels regulations for petroleum fuels.